Lamb’s growth and carcass characteristics as affected by herbaceous or woody pasture in Tunisian North West - Mekki I.; Smeti S.; Hajji H; Mahouachi M.; Trabelsi A.; Atti N. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The aim of this work was to study the effect of rearing system of two mountainous areas, Ain Draham of Woody Pasture (WP) and Fernana of Herbaceous Pasture (HP) on growth and carcass composition of lambs. The WP is characterized by an uneven distribution of plant biomass, with Quercus suber dominates the shrubby stratum which in turn dominates the herbaceous during the period of low rainfall, by cons HP is characterized by grasses and clover. Animals of both regions were fed exclusively on pasture which amount and value depends on the production potential of the rearing systems. They were weighted monthly from birth until 4 months age where 10 lambs from each region were slaughtered and the left shoulders were dissected. The final live weight and average daily gain were affected by pasture type. The slaughter body weight was 28.6 kg and 23.8 kg for HP and WP respectively. The carcass weight was higher (p = 0.003) on HP than WP (14.1 vs 10.9 kg). Consequently, the commercial yield was 49% for HP and 46% for WP. Fat content was 11 and 15% for WP and HP, respectively, while bone content was higher for sheep from WP. The WP group presents a higher quantity of muscle than HP group (64% vs 62%). This composition resulted from the difference in the slaughter body weight.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)